Interval Open Necrosectomy: Case Report - Carrillo-Pinto, Laura Daniela Caridad; Vidales-López, Raúl Alfonso; Flores-López, Alejandro Alberto; Espinosa-Rosales, Alicia Valeria; Falcón-Cancino, Luis Arturo (British Journal of Healthcare and Medical Research, 2023)
Background: Acute pancreatitis is caused by intrapancreatic enzymatic activation, this leads to inflammation and destruction of the pancreas, most patients have a mild edematous course with low mortality, infection of the necrotized pancreas is usually associated with a severe course and higher mortality. Clinical case: We present the case of a 47-year-old male presenting with acute necrotizing pancreatitis complicated with infection without organ failure. The purpose of this article is to present the role of open necrosectomy in the management and review of literature. Discussion: The main indication for drainage and debridement in necrotizing pancreatitis is the presence of infection or clinical deterioration in case sterile necrosis and should be postponed optimally > 4 weeks into the course of the disease for adequate limitation of the necrosis and improved physiological condition. Conclusion: While a step-up minimally invasive approach is recommended to open necrosectomy, this is not always possible; open necrosectomy still is a valid alternative for the management of the disease.